2014
DOI: 10.1097/qad.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Delayed HIV diagnosis and initiation of antiretroviral therapy

Abstract: Socioeconomic inequalities in delayed HIV diagnosis and initiation of cART are present in European countries with universal healthcare systems and individuals with lower educational level do not equally benefit from timely cART initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 32 publications
3
14
1
1
Order By: Relevance
“…This explanation is emphasized by our results about the reason for HIV testing, showing that patients diagnosed by clinical suspicion were 5 times more likely to be . This observation could be explained by the fact that outreach campaigns, were more understandable for those who were enrolled in school and they were therefore screened earlier [27]. Location was not associated to late presentation in our study.…”
Section: Factors Associated With Late Presentationcontrasting
confidence: 35%
“…This explanation is emphasized by our results about the reason for HIV testing, showing that patients diagnosed by clinical suspicion were 5 times more likely to be . This observation could be explained by the fact that outreach campaigns, were more understandable for those who were enrolled in school and they were therefore screened earlier [27]. Location was not associated to late presentation in our study.…”
Section: Factors Associated With Late Presentationcontrasting
confidence: 35%
“…People presenting late often declare that they were not ill, although the majority of them were symptomatic during the year preceding HIV diagnosis and consulted a physician for these symptoms [32]. In other cases (as among foreign patients, women and IDUs), socioeconomic status and poor access to health care may have contributed to late presentation [37, 38]. At the same time, it is possible that some other factors may contribute to decreased use of condoms, either among heterosexuals or MSM, as alcohol abuse and/or illicit drug use.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the critical role of ART, there are widespread inequalities in accessing and utilizing this service [11–14]. International research suggests that lower socioeconomic status (SES) was closely related to delayed ART initiation, lower treatment adherence, and poorer outcomes [11–14].…”
Section: Introductionmentioning
confidence: 99%
“…International research suggests that lower socioeconomic status (SES) was closely related to delayed ART initiation, lower treatment adherence, and poorer outcomes [11–14]. For example, previous studies showed the positive association between education and early HIV diagnosis and ART initiation [11,15,16]. Furthermore, WHO emphasized in “Treatment 2.0” guideline that wealthier PLWH were more likely to have access to better HIV/AIDS care services [17].…”
Section: Introductionmentioning
confidence: 99%